THE INFLUENCE OF USING SHORT STORY TOWARD READING ABILITY AT THE EIGHT GRADE MADRASAH TSANAWIYAH NURUL HUDA, BAROS-SERANG - Lia Amalia (FKIP, Universitas Banten Jaya, 2019)
Method of the research used quantitative research by using quasi experimental design.has both pre and posttests and experimental and control groups, but no random assignment of subjects. To collect the data, the writer used pre-test and post-test. Pre-test given to students before treatment. Post-test is a test that given to students after treatment. After collecting the data, the writer qualifies it based on its kind. To analyze data, the writer uses twoapproaches. To compare the result of research between experimental class and control class.From the calculation of data, the writer got the result as follow: from control class: (1) Mean score of pre-test (My1) 61,8 and post-test score (My2) 72,0. It means that average score of control class got increase 10,2. Whereas mean score from experimental class for pre-test (Mx1) 57,9 and post-testscore (Mx2) 78,3. It means that average score from experimental class got increase 20,4 and it got higher increase than from control class. (2) The percentage from control class is 34% and experimental class is 67%, so both average and percentage score both of control class and experimental class got increase but control class got relatively little increase than experimental class. (3) “t” observation is 6,41 and 70.